(untitled) (Asian Journal of Medical Research and Health Sciences, 2025)
Background: Patient satisfaction is a key indicator of the quality of medical services and overall healthcare performance. It reflects how well healthcare providers meet patients’ expectations regarding care, communication, treatment outcomes, and the hospital environment. Recognizing the growing importance of patient-centered care, this study examines how the quality of services provided by medical staff directly affects patient satisfaction in the hospital, using the SERVQUAL model’s five dimensions: Reliability, Assurance, Tangibles, Empathy, and Responsiveness. Methodology: Our study was a cross-sectional study conducted from April to June 2025 at JSS Hospital, a tertiary-level teaching hospital among 320 patients using a structured questionnaire based on the SERVQUAL model, adapted to the healthcare context. The instrument included 22 items covering five service quality dimensions—Reliability, Assurance, Tangibles, Empathy, and Responsiveness—as well as items measuring overall satisfaction. Results: Results indicated that overall satisfaction was moderate [Mean = 3.32], with Responsiveness [2.53] and Empathy [2.50] scoring the highest, and Assurance [2.41] and Tangibles [2.39] scoring the lowest. A moderately strong positive relationship [R = 0.647, p < 0.001] existed between service quality and satisfaction, with the model accounting for 41.9% of the variance [R² = 0.419]. Regression showed Reliability, Empathy, and Responsiveness as significant predictors [p < 0.05]; Assurance and Tangibles were not. Conclusion: These findings underscore that enhancing Reliability, Empathy, and Responsiveness is crucial for increasing patient satisfaction, guiding administrators on where to focus improvements for better patient-centered care.